Interconnectivity of Leadership: An Analysis of the Synergistic Role of Village Leadership in Education Development - Prasetya, Subhan Muhajir; Aufa, Rinjani (Development: Studies in Educational Management and Leadership, 2023)
The study focuses on investigating the relationship between leadership functions and employee performance, specifically addressing the issue of employee arrogance. The researcher employed qualitative research methods, utilizing purposive sampling to select suitable respondents. The study collected primary data through interviews, observations, and documentation, supplemented by secondary data. The researcher served as the main instrument, employing interview guidelines and recording field notes for data collection. The data analysis followed Miles & Huberman's approach, involving data reduction, data display, and conclusion drawing. The findings of the research indicate that effective leadership functions play a vital role in reducing employee arrogance. These leadership functions encompass instructive, consultative, participative, delegative, and controlling functions. The study also highlights the leadership's assertiveness in decision-making to fulfill employees' core tasks and functions, emphasizing the importance of monthly socialization methods. Additionally, factors such as work motivation, education, and work experience of employees were found to contribute to reducing arrogance. On the other hand, inhibiting factors include the lack of adequate facilities and infrastructure that support a comfortable work environment. Overall, these factors significantly impact employee attitudes, work discipline, and overall performance